Utilisation of preventative health check-ups in the UK: findings from individual-level repeated cross-sectional data from 1992 to 2008. Issue 12 (23rd December 2013) - Labeit, Alexander; Peinemann, Frank; Baker, Richard
Abstract : Objectives: To analyse and compare the determinants of screening uptake for different National Health Service (NHS) health check-ups in the UK. Design: Individual-level analysis of repeated cross-sectional surveys with balanced panel data. Setting: The UK. Participants: Individuals taking part in the British Household Panel Survey (BHPS), 1992–2008. Outcome measure: Uptake of NHS health check-ups for cervical cancer screening, breast cancer screening, blood pressure checks, cholesterol tests, dental screening and eyesight tests. Methods: Dynamic panel data models (random effects panel probit with initial conditions). Results: Having had a health check-up 1 year before, and previously in accordance with the recommended schedule, was associated with higher uptake of health check-ups. Individuals who visited a general practitioner (GP) had a significantly higher uptake in 5 of the 6 health check-ups. Uptake was highest in the recommended age group for breast and cervical cancer screening. For all health check-ups, age had a non-linear relationship. Lower self-rated health status was associated with increased uptake of blood pressure checks and cholesterol tests; smoking was associated with decreased uptake of 4 health check-ups. The effects of socioeconomic variables differed for the different health check-ups. Ethnicity did not have a significant influence on any health check-up. Permanent household income had an influence only on eyesight tests and dental screening. Conclusions: Common determinants for having health check-ups are age, screening history and a GP visit. Policy interventions to increase uptake should consider the central role of the GP in promoting screening examinations and in preserving a high level of uptake. Possible economic barriers to access for prevention exist for dental screening and eyesight tests, and could be a target for policy intervention. Trial registration: This observational study was not registered.